Early Experience of Percutaneous Transhepatic Biliary Stenting in Malignant Biliary Obstruction in Nepal - Thapa, Ajit; Suwal, Sundar; Chataut, Dinesh; Subedi, Kamal (Nepalese Journal of Radiology, 2018)
Introduction: Percutaneous biliary stenting is recommended for palliation of unresectable malignant biliary obstruction with short life expectancy. Percutaneous biliary stenting is newer interventional imaging guided procedure being practiced in Nepal. Aim of this study is to share our early experience of percutaneous biliary stenting and its complications in Nepal. Methods: Retrospective review of clinical success, complication, stent patency and survival was done in 31 patients with nonoperable malignant biliary obstruction who underwent percutaneous transhepatic metallic biliary stenting from August 2016 to July 2018 Results: We successfully stented 31 malignant biliary obstructions, following external biliary drainage via sonography and fluoroscopy guidance, one week prior to the stenting. The patients were followed up for documentation and management of any complications related to the procedure. Cent percent reduction in bilirubin levels <50% after 2 weeks were achieved. Procedure related mortality was nil. Major complications including early stent block were seen in 7 patients, which we managed accordingly. Stent patency rate for 3 months was 73% and for 6 months was 45%. Although the procedure is recommended in short life expectancy patients, average survival of the patients in our experience was 7.1 months after the procedure with 2 of the patients survived >12 months after the procedure. Conclusion: Percutaneous biliary stenting is less invasive palliation for unresectable malignant biliary obstruction with less complication as well.